Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1108/maj-08-2014-1072
|View full text |Cite
|
Sign up to set email alerts
|

A synthesis of empirical internal audit effectiveness literature pointing to new research opportunities

Abstract: Purpose – The purpose of this paper is to provide a synopsis of what academic literature says about internal audit (IA) effectiveness ten years after Bailey et al. (2003) presented research opportunities in IA. A new set of research questions that may help to bring the best out of IA is proposed. Design/methodology/approach – Empirical studies based on internal auditors’ self-assessments (“inside-out”) and empirical studies based on othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
184
2
12

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(209 citation statements)
references
References 66 publications
11
184
2
12
Order By: Relevance
“…Third, our study addresses calls to better understand the benefits of coordination between internal and external auditors from the internal auditors' perspective (e.g. Gramling et al, 2004;Lenz and Hahn, 2015). Our findings complement prior research by providing evidence that the coordination between the two audit groups helps internal auditors improve their assurance-related assessments.…”
Section: Introductionsupporting
confidence: 75%
“…Third, our study addresses calls to better understand the benefits of coordination between internal and external auditors from the internal auditors' perspective (e.g. Gramling et al, 2004;Lenz and Hahn, 2015). Our findings complement prior research by providing evidence that the coordination between the two audit groups helps internal auditors improve their assurance-related assessments.…”
Section: Introductionsupporting
confidence: 75%
“…The framework to assess convergence is drawn on neo-institutional theory. Owing to the unavailability on publicly disclosed data on IA (Al-Najjar, 2011), the complexities of analysing the linkage between corporate governance measures and the degree of IA effectiveness (Regoliosi & d'Eri, 2014) and doubt expressed over the possibility of generalising the relationship between IA and corporate governance measures (Carcello, Hermanson & Raghunandan, 2005), this study departs from previous research by attempting to "abandon old trails and try new ways", as suggested by Lenz and Hahn (2015). It uses the responses of participants from the BRICS countries on the 2010 global Common Body of Knowledge (CBOK) survey of the Institute of Internal Auditors (IIA) (IIARF, 2010) in conjunction with the elements of the Internal Audit Capability Model (IA-CM).…”
Section: Introductionmentioning
confidence: 63%
“…In one of the latest studies, Lenz and Hahn (2015) performed a synthesis of empirical IA effectiveness literature and suggested that IA effectiveness should be viewed as a multifaceted concept which distinguishes between macro and micro dimensions. They identified micro dimensions as the organisation, IA resources, IA processes and IA relationships.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence and proliferation of auditing shows that traditional central control in government is still possible. Whether auditing is particularly successful or unsuccessful is beyond the scope of the present research (but see Lenz & Hahn, 2015;Nuijten et al, 2015). Presumably the same holds for auditors as would hold for the members of most other professions-some are very good, others are not.…”
Section: Conclusion and Discussionmentioning
confidence: 98%